Fluctuations of the Black Sea level in Neoeuxine-Holocene versus catastrophic flood hypothesis - Konikov, E.; Faschevsky, S.; Pedan, G. (Геология и полезные ископаемые Мирового океана, 2009)
This paper presents the pictures of paleogeography and variations of sea level of the Black Sea basin in Neoeuxinian and Holocenian stages under discussion relative to the hypothesis of catastrophic flooding presented by Ryan W et.al. (1997, 2001). Based on lithologic genetic analysis of sediments, biostratigraphy, absolute dating tests and chemical composition of interstitual water on the shelf and estuaries, paleographyc maps for the main events of the Late Neoeuxinian Holocenian history of basin was constracted. It is given evedences against probability of catastrophic flooding in the early stage of Neoeuxinian transgression and over Holocene.